LATITUDE EFFECT OF THE COSMIC RAY NUCLEON AND MESON COMPONENTS AT SEA LEVEL FROM THE ARCTIC TO THE ANTARCTIC - Rose, D. C.; Fenton, K. B.; Katzman, J.; Simpson, J. A. (Canadian Journal of Physics, 1956)
Results are presented of cosmic ray measurements taken at sea level during 1954–55 from the Arctic to the Antarctic. The equipment consisted of a neutron monitor and a meson telescope. Latitude effects of 1.77 for the nucleonic component and 1.15 for the meson component were measured. The longitude effect at the equator was much less than expected on the basis of the geomagnetic eccentric dipole and the longitude effect at intermediate northern latitudes shows that the longitude of the effective eccentric dipole is considerably west of that of the geomagnetic eccentric dipole. In a previous paper by the same authors, the positions of the equatorial minima were combined with other published cosmic ray measurements to calculate a new cosmic ray geomagnetic equator. In this paper new coordinates are derived on the assumption that these equatorial coordinates apply to a new eccentric dipole, and, therefore, that the equatorial coordinates may be extended to high latitudes. When the complete results are plotted on these coordinates, it is found that an eccentric dipole representation of the earth's magnetic field is inconsistent with the combined observations at all latitudes.